MAKNA DAN IDENTITAS BUDAYA BAJAWA NUSA TENGGARA TIMUR DALAM FILM SAHABAT KECIL EPISODE 2 - Apolonius Kristoforus Ga’a; Fathul Qorib; M Abd Ghofur (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2022)
The film “Childhood Friend episode 2” is a film telling the story about the love of a couple who had to run aground because of the differences in social caste between the two families. The reason for choosing the film " Childhood Friend episode 2" is because in the film it displays elements of Bajawa (East Nusa Tenggara) culture. The purpose of this research is to find out the meaning of Bajawa cultural symbols contained in the scenes in the film. This study uses a qualitative research method using the method of semiotic analysis of the meaning triangle of Charles Sanders Pierce. Based on the results of this study, there is the meaning of the Bajawa cultural symbol like a traditional house Ngadhu, Bagha, traditional clothes like Boku, Kasa sese and the Bajawa traditional marriage system. For readers to be able to understand and tolerate each other with friends from different cultures so that there are no misunderstandings and miscommunications so that conflicts do not occur.Film “Sahabat Kecil episode 2” merupakan film yang bercerita tentang cinta sepasang kekasih yang harus kandas karena perbedaan kasta sosial antara kedua keluarga. Alasan memilih film “Sahabat Kecil episode 2” karena dalam film tersebut menampilkan unsur kebudayaan Bajawa (Nusa Tenggara Timur). Tujuan dalam penelitian ini untuk mengetahui makna simbol-simbol budaya Bajawa yang terdapat dalam scene-scene dalam film tersebut. Penelitian ini menggunakan metode penelitian kualitatif dengan menggunakan metode analisis semiotika segitiga makna Charles Sanders Pierce. Berdasarkan hasil penelitian ini, terdapat makna simbol budaya Bajawa seperti rumah adat Ngadhu, Bagha, pakaian adat seperti Boku, kasa sesedan sistem perkawinan adat Bajawa. Bagi para pembaca agar mampu memahami dan saling bertoleransi dengan teman yang berbeda budaya agar tidak terjadi kesalahpahaman dan miskomunikasi sehingga tidak terjadinya konflik.